Analisis Sistem Informasi Akuntansi Penerimaan KAS Pada PT Daelova Indonesia - Nuramdani; Asep Suherman (Prisani Cendekia, 2022)
The purpose of this reseacrch is to. 1) to find out the cash receipts accounting information system at PT Dealova Indonesia, and 2) to determine the internal control of cash receipts at PT Dealova Indonesia. This research methodis qualitative with interview, documentation data collection methods. The results of this study found that the cash receipts accounting information system at PT Dealova Indonesia can be said to have been implemented well. Control activities over cash receipts at PT Dealova Indonesia are not fully adequate, this can be seen in the absence of a separation of functions in the warehouse and shipping section because the sales department is still preparing goods. The separation of functions is carried out to avoid unhealthy practices, especially in the sales departement because it receives cash directly from customers. While the document used are incomplete. Asset security is quite adequate, namely the existence of authorization, namely making orders only by the sales departement.